PENGELOLAAN HAK KEKAYAAN INTELEKTUAL SEBAGAI STRATEGI KEUNGGULAN PERUSAHAAN STUDI KASUS : PT CIPTA SARANA KENAYU LESTARI - , Septilina Melati Sirait ([Yogyakarta] : Universitas Gadjah Mada, 2013)
PT Cipta Sarana Kenayu Lestari is one of growing cosmetic companies and has already obtained the certificate Good Cosmetic Manufacturing Practice (GCMP) in 2009. This company classified as Small and Medium Enterprises (SMEs) is always improving its performance for facing the dynamic environment. PT CSKL always enhance creativity and innovation in order to create an advantage for survival. Every company needs a knowledge-based management including knowledge in managing intellectual property in order to make innovation continuously to anticipate the changing dynamically environment. The purpose of this research is to assess intellectual property management to be used as a strategy of corporate advantage. This research is a kind of qualitative study produced the descriptive data in a form of the written words or spoken from the study subjects. Subjects were selected by purposive sampling are the top management of PT CSKL. The method to collect the data were used interview method, observation, documentation and library study. Then systematically analyzed by arranging the data from each method of data collection and make a conclusion thus easily understood by myself and others. The result shows that PT CSKL has managed many innovations both of product and process innovation. PT CSKL aware the important of innovation and IPR protection into business process by registering to the Director General of Intelectual Property Rights (IPRs). However, from the existing regime, PT CSKL only manages brand and trade secret. This is because of limited cost and facilities classified as a small and medium enterprises, then there are some which not be registered such as logoâs company, formula of honey lipstick, website, brochure and packaging design. IPR protected by law is used as a strategy advantage of PT CSKL in doing business development strategy. This strategy starts from the management of innovation in family firms into strategic corporate level towards good corporate governance and cooperation strategic alliance, followed by a strategic business level towards to Porterâs focus strategic and competitive strategic as industrial fragmented and strategic level functional in production, marketing, finance and R&D and QC.